Mechanical Characterization of Metal–Polymer Joints Fabricated via Thermal Direct Bonding Technique - Chiara Morano; Andrea Morabito; Luigi Bruno; Marco Alfano; Leonardo Pagnotta (Engineering Proceedings)
In recent years, thermoplastic polymers and composites have seen increasing application across various industrial sectors to develop lightweight structures. These materials have gained popularity in the market due to advancements in additive manufacturing. Thermal direct joining serves as an effective solution for integrating such thermoplastic materials into existing or de-novo metal structures. This method enables the creation of lightweight and virtually reversible joints, which foster end-of-life recyclability, thus aligning with the principles of a circular economy. However, these joints are still affected by a low strength, which is mostly related to the poor polymer–metal interaction. The use of surface treatments that promote mechanical interlocking of the polymer within surface asperities in the mating metallic adherend can be an effective strategy to enhance the strength, as well as to improve the toughness and damage tolerance of the joints. In this work, a laser treatment was used to modify the surface texture of an aluminum sheet prior to thermal bonding with 3D-printed polylactic acid (PLA). Different surface textures were analyzed by modifying the main process parameters. Roughness and wettability measurements were performed to identify the most effective processing condition. Finally, mechanical tests were performed to verify the improvement in joint resistance obtained by interface modification.